What Factors Matter for the Evaluation of Relationship between the Perceptions of Corruption and Politicization in Local Administration in Poland - Piotrowska, Maria (Jakie czynniki mają znaczenie dla oceny związku między korupcją a naciskami politycznymi w administracji lokalnej w Polsce, 2010)
The main purpose of the paper is to identify factors that can matter for the relationship between perceptions of corruption and politicization by the public service officials at the local administration level in Poland. Four groups of factors are considered: 1) the structure of administration, 2) citizen voice as an "external" (to public sector) factor, 3) agency characteristics, and 4) individual characteristics. The research is based on a questionnaire survey of 858 public officials working in 100 commune councils in Poland in 2009. The findings based on the correlation analysis show that the location of a commune council and a type of a commune councils strongly influence the relationship between politicization and corruption.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 138-149
Keywords: politicization; corruption; local administration